Indonesian manuscripts in Iran. Issue 143 (2nd January 2021) - Daneshgar, Majid
ABSTRACT: This report aims to introduce three previously unknown and under-examined Indonesian manuscripts that are preserved in Iranian libraries. They are written on dluwang/daluang paper and each include interlinear translations and glosses in Javanese using Pégon script. These manuscripts had been in the possession of religious families in Iran.